2020
DOI: 10.1002/chem.202000982
|View full text |Cite
|
Sign up to set email alerts
|

Yield—not only Lifetime—of the Photoinduced Charge‐Separated State in Iridium Complex–Polyoxometalate Dyads Impact Their Hydrogen Evolution Reactivity

Abstract: Covalently linked photosensitizer–polyoxometalate (PS‐POM) dyads are promising molecular systems for light‐induced energy conversion processes, such as “solar” hydrogen generation. To date, very little is known of their fundamental photophysical properties which affect the catalytic reactivity and stability of the systems. PS‐POM dyads often feature short‐lived photoinduced charge‐separated states, and the lifetimes of these states are considered crucial for the function of PS‐POM dyads in molecular photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The team demonstrated that variation of the central heterometal (Fe 3+ , Co 3+ , Mn 3+ ) of the Anderson anion can be used to tune the light‐driven hydrogen evolution of these systems. Further, detailed time‐resolved optical spectroscopy and spectro‐electrochemistry demonstrated the charge‐separation pathways [28] and identified limiting processes for the hydrogen evolution catalysis [29] …”
Section: Introductionmentioning
confidence: 99%
“…The team demonstrated that variation of the central heterometal (Fe 3+ , Co 3+ , Mn 3+ ) of the Anderson anion can be used to tune the light‐driven hydrogen evolution of these systems. Further, detailed time‐resolved optical spectroscopy and spectro‐electrochemistry demonstrated the charge‐separation pathways [28] and identified limiting processes for the hydrogen evolution catalysis [29] …”
Section: Introductionmentioning
confidence: 99%
“…Most studies on visible-light driven photoredoxc atalysis completely ignore the efficiency aspect (i.e.,t he overall quantum yields) and merely focus on the feasibility to use visible light as energy input. In addition to photoredox catalysis, the M À generation is important for many photochemical carbon dioxide reduction [12,[81][82][83] and hydrogen production [13,[84][85][86][87][88][89][90][91][92] mechanisms, demonstrating that the new mechanism introduced in this manuscript has severalp ossible application areas. Our study on the heavily underexplored inherente ffi-ciency of photoinduced electron transfer events might trigger furtherq uantitative investigations that could contribute to a better understanding of how to use photons moree fficiently, [93] which could ultimately result in more sustainability in photochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, light-driven catalytic studies were performed in water-free, de-aerated DMF solutions containing the respective catalyst POM-PtX (12.5 µM), the photosensitizer PS (125 M) and triethyl amine/acetic acid (TEA (1.0 M) / HAc (0.2 M)) as sacrificial proton/electron donors; this experimental setup has been adapted from earlier POM-based HER studies. 44,[46][47][48] The samples were irradiated under an Ar atmosphere using monochromatic LEDs (λmax = 470 nm, P ~ 40 mW cm -2 ) at 25°C. Hydrogen evolution was quantified by calibrated gas chromatography.…”
Section: Light-driven Hydrogen Evolutionmentioning
confidence: 99%